2020
DOI: 10.1108/ijchm-05-2019-0464
|View full text |Cite
|
Sign up to set email alerts
|

It’s not all about price. The determinants of occupancy rates in peer-to-peer accommodation

Abstract: Purpose This paper aims to identify the key drivers of occupancy rates in peer-to-peer accommodation. Design/methodology/approach The applied methodology fits the specific characteristics of this market segment: the peculiar distribution of the occupancy rate (a ratio characterised by a large share of zeros) requires the adoption of a mixed discrete-continuous model; the insidious issue of price endogeneity is dealt with a control function approach; the econometric specification takes into account the monopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…From the review of published literature reviews, existing studies have found that the volume and rate scores of online reputations are key and steady determinants influencing consumers' booking behaviors (Leoni et al , 2020; Purnawirawan et al , 2015; Zhao et al , 2015). Dynamic pricing and price conscientiousness were also widely investigated in the online accommodation booking context (Guizzardi et al , 2019).…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…From the review of published literature reviews, existing studies have found that the volume and rate scores of online reputations are key and steady determinants influencing consumers' booking behaviors (Leoni et al , 2020; Purnawirawan et al , 2015; Zhao et al , 2015). Dynamic pricing and price conscientiousness were also widely investigated in the online accommodation booking context (Guizzardi et al , 2019).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Discount strategy includes three tiers in our study, including direct (Huang, 2016) and price-break discounts (Kim and Hwang, 1988) and coupons (Guimond et al , 2011). Online review number connotes the number of reviews the listing has accumulated (Leoni et al , 2020). Online review number also includes three different tiers: high, medium and low.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The fourth stream highlights the impact of P2P accommodation on hotel revenue (Xie and Kwok, 2017). The fifth stream highlights the determinants of P2P accommodation performance (Leoni et al , 2020; Ranjbari et al , 2020). Hence, our literature review makes two prominent observations.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Therefore, new models based on more complex patterns are needed. Other promising avenues of research are the use of locational models (Zhang et al, 2017), multivariate regression models that are able to apply selected independent and control variables to more than one outcome variable and non-linear models (Leoni et al, 2020).…”
Section: Theoretical Conclusionmentioning
confidence: 99%